CHRONIC URTICARIA IN CHILDREN: A REVIEW - Blanca R. Del Pozzo-Magaña (European Medical Journal, 2017)
Chronic urticaria (CU) is characterised by the recurrence of hives/angioedema for >6 weeks. It affects children and adults and has a worldwide distribution. In children, CU is substantially less common than acute urticaria but is associated with larger decrease in quality of life. The current classification divides CU into two groups: 1) chronic spontaneous urticaria, which includes idiopathic urticaria (by far the most common type), autoimmune urticaria, and those associated with drugs, food, or additives allergies; and 2) chronic inducible urticaria, constituted by cholinergic urticaria and physical urticarias. Diagnosis of CU is based on the history and characteristics of the lesions. Although laboratory and specific testing could establish the diagnosis of some subtypes of CU, frequently the aetiology is never found; therefore, an extensive workup is not recommended. Once the trigger has been identified, it must be avoided. Specific treatment may be tried, but unfortunately this is not always possible. Currently, the first-line treatment for children with CU are second generation H1-antihistamines (SG-H1AH), such as cetirizine, fexofenadine, desloratadine, and rupatadine, among others. If, after 2-4 weeks, the patient has not improved, an increment from 2 to 4-times the regular dose is recommended. Patients that fail to respond to this treatment may be switched to another SG-H1AH or a second agent, such as H2-antihistamines (e.g., cimetidine, ranitidine), ketotifen, cyclosporine, or a leukotriene receptor inhibitor (e.g., montelukast), may be added to the H1-antihistamine therapy. Recently, omalizumab, an anti-immunoglobin-E monoclonal antibody has been approved in several jurisdictions for patients 12 years or older with recalcitrant CU; however, its high cost has limited its use.